IN VIVO STUDY ON DIURETIC AND LAXATIVE THERAPEUTIC PROPERTIES OF HYDRO - ALCOHOLIC EXTRACT OF LU HUI (LILLIACEAE) ON EXPERIMENTAL RODENTS (RATTUS NORVEGICUS). - RAO US, MAHADEVA; ZIN, THANT (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: In furtherance to the rising evidences for therapeutical potential of Lu Hui (Aloe vera), the existing study was carried out to evaluate the diuretic and laxative activity of its hydro-alcoholic extract on rodents. Materials and Methods: The hydro-alcoholic extract of leaves of Lu Hui (HALL) was prepared by using Soxhlet extractor and subjected to analysis by standard preliminary phytochemical tests. Assessment of both the diuretic and laxative activity was carried out using standard methods. Furosemide (20 mg/kg) was functioned as a positive control for diuretic activity, whereas gaviscon (10 mg/kg) worked as a reference drug for laxative activity. Results: The HALL showed weight diuretic activity and found to be the most potent in increasing the urinary output at 600 mg/kg when the effect was comparable to that of the standard furosemide. Besides, this extract found to be most effective in increasing urinary electrolyte concentration (sodium, potassium, chloride) at both the doses tested. On the other hand, the results for laxative activity exhibited incredible increase of feces output at the dose of 600 mg/kg, and the increase was similar to that of standard drug gaviscon. Conclusion: Altogether, the above major findings validate and support its folkloric diuretic and purgative use and lend pharmacological credence to the ethnomedical use of this leaves in the traditional system of medicine, stresses further studies to intricate its active constituents, uses and safety. Keywords: Bioassay, Diuretic, Laxative, Furosemide, Gaviscon, Ethnomedicine.